PERSEPSI KHALAYAK TERHADAP PENGGUNAAN STRATEGI HUMOR IKLAN TELEVISI DJARUM 76 VERSI TERDAMPAR DI PULAU - Putra, Aries Aditya (Universitas Prof. Dr. Moestopo (Beragama), 2013)
To display the advertising message that is able to induce and maintain consumer memory products will be offered,requiring a commercial appeal through creative strategies. Advertising appeal is divided into two, the rationalappeal advertising and advertising appeal is based on feelings and emotions.Forms of creative strategies used to consist of a variety of advertisers, one of which is the use of the creativeaspects of humor. Creative aspects of advertising that uses humor in advertising their products on television certainlycan cause a difference in the perception of the audience. Because of the particular advertising marketingcommunications activities, problems that commonly occur advertising message is delivered can not be capturedwell by the communicant as perceived differently.In this paper, the authors set forth a problem of Audience Perception Strategies Against Use of Humour TelevisionAdvertising Djarum 76 version Stranded on the island. This study aimed to determine differences in publicperceptions based on characteristics seen in terms of gender, age, level of education, type of work, the level ofexpenditure and utilization of spare time on the use of humor in television advertising Djarum 76 version strandedon the island.The theory used in this thesis is the theory of SOR and Individual Differences. The study was descriptive, withquantitative research methods that the object of research is RW.17 Village residents Baktijaya. Authors take thepopulation of people aged over 17 years, amounting to a total of 1077 with a sample of 92 people.Data collection techniques used were questionnaires and literature. And the process of this research using thistype of quantitative data. Based on the data obtained, then be analyzed to count statistically using Chi Squareformula is processed using SPSS.Based on the research that has been conducted and the results of the analysis, that there are differences in theperception of the public towards the use of humor in television advertising Djarum 76 version stranded on theisland (survey residents RW.17Kelurahan Baktijaya) based on the characteristics of gender, occupation and useof leisure time. While the characteristics of age, education level, and monthly expenses no difference.